Vitamin D3 alleviates nonalcoholic fatty liver disease in rats by inhibiting hepatic oxidative stress and inflammation via the SREBP-1-c/ PPARα-NF-κB/IR-S2 signaling pathway - Reda, Doha; Elshopakey, Gehad E.; Albukhari, Talat A.; Almehmadi, Samah J.; Refaat, Bassem; Risha, Engy F.; Mahgoub, Hebatallah A.; El-Boshy, Mohamed E.; Abdelhamid, Fatma M. (Frontiers in Pharmacology, 2023)
Introduction: Non-alcoholic fatty liver disease (NAFLD) is a chronic disease characterized by fat deposits in liver cells that can lead to hepatitis and fibrosis. This study attempted to explore the protective effect of vitamin D3 (VitD) against NAFLD. Methods: Adult male albino rats were randomized into 4 separate groups: negative control group was fed a standard rat chow, positive group received a high-fat diet (20%) and 25% fructose water (NAFLD), VitD control group intramuscularly treated with VitD (1000 IU /kg BW) three days per week for 10 weeks, and the NAFLD group treated with VitD therapy. Biochemical and hepatic histological analyses were performed. Hepatic oxidative stress and inflammatory conditions were also studied. Hepatic expression of sterol regulatory element binding protein 1-c (SREBP-1-c), peroxisome proliferated activated receptor alpha (PPARα), and insulin receptor substrate-2 (IRs-2) were analyzed by quantitative real-time polymerase chain reaction. Results and discussion: The NAFLD rats exhibited elevation in their terminal body weight, hepatic injury markers, dyslipidemia, glucose intolerance, and insulin resistance. Moreover, NAFLD rats had increased SREBP-1-c expression, and reduced PPARα, and IR-S2 expressions. Histological analysis showed hepatic steatosis, and inflammation in the NAFLD group. In contrast, VitD administration improved serum biochemical parameters and hepatic redox status in NAFLD rats. Also, VitD treatment ameliorated hepatic inflammation and steatosis in the NAFLD group by decreasing the expression of SREBP-1-c and increasing the expression of PPARα. Overall, these results suggest that VitD could have a protective effect against NAFLD and its associated complication